Evaluation of Different Water Quality Parameters for Tigris River and Compare with Tap Water for Different Areas in Baghdad (Journal of the College of Basic Education, 2022)
In this research effect of some chemical and physical parameters for Tigirs river in Baghdad City in Summer for April mouth -2012 was studied.(11) samples had been taken for this river and tap water. Water samples were collected from different depths. PH, electrical conductivity (EC),and total dissolved salts(TDS) were studied ,nitrate ion was evaluated by spectroscopic method while chloride , carbonate , bicarbonate , magnesium and Calcium where evaluated by titration method . Sodium, Potassium ions were evaluated by Flame Photometer. The concentrations of ions were found to being the ranges (0.15-4.3) for nitrates in river,( 0.1-9.27) in tap water. And for calcium and magnesium were found to being the ranges (65-145),(205-265) mg /L respectively in river,(69-87),(232.5-318.5) mg /L in tap water.(84.2-119.6) mg /L for chlorides in river,(62.04-88.6) in tap water.(4-8),(4-30) mg /L for carbonate and bicarbonate in river respectively.(4-10),(10-20) mg /L in tap water .(142-345),(2-9) mg /L for Sodium and Potassium respectively in river,(142-190) ),(1.59-6) mg /L in tap water. And PH values( 6.69-9.04), EC ( 0.44-1.07) µs/cm and TDS ( 227.22-573.3) mg/L. From this research many parameters were studied to know quality of water. Value for River in maximum that lead to a pollution in these area . The River water was alkanity and environmental pollution.